The Effect of Socialization Externalization Conbination Internalization Methods in Improving the Implementation of Early Mobilization in Inpatient Wards - Karnadi Karnadi; Suyanto Suyanto; Erna Melastuti; Herry Susanto (GLOBAL HEALTH SCIENCE GROUP, 2025)
Early mobilization is a therapeutic approach involving physical activity or patient mobilization that begins early after medical procedures, such as surgery, especially in the context of intensive care unit (ICU) care. The purpose of this study was to prevent complications associated with immobility, such as muscle weakness, decreased physical function, and cardiovascular problems, and to accelerate patient recovery. The research method used a literature review with a search for relevant articles using semantic science. This study is in accordance with the keywords that have been found and refers to the criteria for dysarthria and speech therapy, the overall search results for articles from 3 databases contained 350 articles. After filtering the full text obtained 10 journals from scientific articles published in the last 5 years (2019-2024), which showed that there was an influence of the externalization socialization method combined with internalization in improving the implementation of early mobilization in the inpatient ward. Research with an orthogonal design showed no influence of the externalization socialization method combined with internalization in improving the implementation of early mobilization.